The PaCES (Palliative Care Early and Systematic) Project: Impact of individual components of a multi-faceted intervention on early referral to specialist palliative care. Issue 28 (1st October 2022) - Sinnarajah, Aynharan; Earp, Madalene; Biondo, Patricia; Piquette, Camille; Vandale, Janet; Tang, Patricia A.; Kerba, Marc; Watanabe, Sharon; Tan, Amy; Simon, Jessica
Abstract : 199 Background: Early referral to specialist palliative care can improve, or maintain, symptom and quality of life outcomes that matter most to patients facing life-limiting illnesses. We tested a multifaceted oncologist-facing intervention (Palliative Care Early and Systematic) in the real-world setting of a busy outpatient cancer clinic for its ability to increase the proportion of patients who receive early specialist palliative care (defined as ≥ 90 days before death). Herein, we describe how each component of the multi-faceted intervention, intended to bridge cancer, primary, and palliative care, impacted early use of specialist palliative care among advanced colorectal cancer patients. Methods: Two intervention components were implemented in Calgary, Alberta, Canada's tertiary cancer centre from January 2019 to June 2020: 1) Adult colorectal cancer patients were referred to a community-based Clinical Nurse Specialist if they failed, or could not receive, first-line chemotherapy, or had high symptom burden (indicated by an Edmonton Symptom Assessment System Revised score ≥ 7); 2) Medical oncologists sent templated 'Shared Care' letters to patients' primary care providers to improve communication, collaboration and role clarity. Results: N = 209 eligible patients died during the intervention period, of whom 57% experienced early referral to specialist palliative care. The median days from referral to death was 130 (IQR: 53-359). Of the 209, 28 (13%) saw the Clinical Nurse Specialist and received Shared Care letters, and all (100%) had early specialist palliative care referral (median 240 days, IQR: 161-359). 21/209 (10%) saw the Clinical Nurse Specialist but had no Shared Care letter. Of these 21, 76% had early specialist palliative care referral (median 197 days, IQR: 96-251). 43/209 (21%) had a Shared Care letter but no interaction with the Clinical Nurse Specialist. Of these 43, 53% had early specialist palliative care referral (median 102 days, IQR: 53-257). 117/209 (56%) did not interact with the Clinical Nurse Specialist or have a Shared Care letter. Of these 117, 45% had early specialist palliative care referral (median 86 days, IQR: 40-204). Conclusions: The Clinical Nurse Specialist was associated with the greatest increase in early specialist palliative care referral; however, the Clinical Nurse Specialist and Shared Care letters combined were associated with even greater (100%) early specialist palliative care use.